Examining Social and Emotional Relation: Attitude Resources in the Spoken Dialogue of Spellbound (2024) - durotunnasihah durotunnasihah; maisarah ira (Universitas Muhammadiyah Semarang, 2026)
Attitudinal aspect in Appraisal framework focuses on how speakers express and evaluate meaning. Examining how Attitude resources within the Appraisal Framework used to interpret meaning in the animated film Spellbound (2024) is the purpose of this study through identifying the frequency of Attitudinal aspects—Affect, Judgment, and Appreciation—and investigating how characters employ these resources to express emotions, interpret behaviour, and describe situations. A qualitative content analysis approach is applied. The film’s transcript was cleaned, coded and segmented through White & Martin’s (2005) Appraisal Framework. The results reveal Affect is the most dominant category, followed by Judgment and Appreciation lastly appears. This sequence shows that emotional expression has the important roles in shaping how the characters interact each other and influencing the way story develops, while assessing others’ behaviour ad evaluating settings and situation are slightly used to complement the integrated storyline. Attitude resources help significantly character development, interpersonal relationship, and narrative meaning. However, this study is limited on one animated movie and only focused on written script particularly spoken dialogue. Future study can further research by involving multimodal features such analysis of gestures and surrounding environment. Overall, valuable insights into evaluative language in animated film dialogue are provided by the study, highlighting the usefulness of the Appraisal Framework for exploring interpersonal meaning in evaluation discourse.Keywords: Appraisal Framework; Attitudinal Resource; Spellbound (2024); Spoken Dialogue